Exploring Phylogenetic Variability of Blastocystis sp. Isolates in Macaca fascicularis in Indonesia - Wahyuningtyas, Puput Ade; Kristijanto, Edward Yonas (VITEK : Bidang Kedokteran Hewan, 2024)
found in both animals and humans. Long-tailed monkeys have the potential to be a reservoir for the spread of zoonotic diseases. This study aims to molecularly identify Blastocystis sp. The 18S SSU rRNA gene can be used to determine the diversity of subtypes, homology, and phylogenetic analysis of Blastocystis sp. 85 fecal samples of long-tailed monkeys from Alas Purwo National Park, East Java were identified and molecularly confirmed using PCR with the primers BhRDr (5'- GAG CTT TTT AAC TCC AAC AAA CG-3') and RD5 (5'-ATC TGG TTG ATC CTG CCA GT-3'). The PCR results showed three positive samples with amplified bands with a length of 600bp, then DNA sequencing was carried out to analyze the phylogenetics of Blastocystis sp. The sequencing results for sample codes MB7, MB22, and MB9 have the closest level of homology to subtype 1 found in human samples and long-tailed monkeys in several countries. The third isolate from this study was still identical, and considered a local strain species because the third sample was grouped in a separate branch from another country.